Flipped Classroom with Whiteboard Animation to Promote Communication Skill: A Mixed Method Study - Gede Suwardika; Agus Tatang Sopandi; Putu Oktap Indrawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Communication skills are crucial competencies for both teachers and aspiring educators. However, the reality is that the skills of many teachers are not yet adequate. This research aims to analyze the impact of implementing a Flipped Classroom with Whiteboard Animation on students’ communication skills. The research employed a Convergent Mixed Methods Design, where quantitative and qualitative data were collected concurrently and analyzed separately to confirm their relationship. The participants consisted of 83 students who were elementary school teachers taking the Science Education course. Quantitative data on communication skills were gathered using the ICCS questionnaire, while qualitative data were obtained through observations, completion of student worksheets, and interviews. Quantitative data were analyzed using ANCOVA, while qualitative data underwent qualitative descriptive analysis. The research findings demonstrated that Flipped Classroom with Whiteboard Animation effectively enhanced students’ communication skills through the instructional steps during the webinar. These findings indicate that Flipped Classroom with whiteboard animation can be considered an effective alternative for improving students’ communication skills.